Ethnic perceptions of Acadia - Williams, Colin (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1977)
The name Acadia, given to a portion of the Atlantic region of North America, connotes a wide variety of territorial referents. From the results of a survey of a sample of New Brunswick high school students, it was determined that the exact nature and extent of the area known under the name of Acadia varied, depending on the sample location and ethnic affiliation of the respondants. But a core area common to all samples is centered on Moncton and its immediate hinterland.